Biliverdin reductase A is a major determinant of protective NRF2 signaling - Chirag Vasavda; Ruchita Kothari; Navneet Ammal Kaidery; Suwarna Chakraborty; Sunil Jamuna Tripathi; Ryan S. Dhindsa; Cristina Ricco; Shruthi Shanmukha; Samaneh Saberi; Julia E. Lefler; Priyanka Kothari; Kalyani Chaubey; et al. (Proceedings of the National Academy of Sciences, 2025)
Biliverdin reductase A (BVRA), the terminal enzyme in heme catabolism, generates the neuroprotective and lipophilic antioxidant bilirubin. Here, we identify a nonenzymatic role for BVRA in redox regulation. Through phylogenetic, genetic, biochemical, and enzymatic assays, we found that BVRA exerts critical nonenzymatic antioxidant activity. Transcriptomic analyses further revealed that BVRA physically and genetically interacts with nuclear factor erythroid-derived factor-like 2 (NRF2), a major transcriptional regulator of cellular redox signaling. ChIP-seq and RNA-seq analyses reveal that BVRA and NRF2 coordinate the expression of antioxidant genes, many of which are typically dysregulated in neurodegenerative conditions such as Alzheimer’s disease. Thus, this noncanonical BVRA–NRF2 axis controls an essential pathway of redox signaling in neuroprotection. Our findings position BVRA as a dual-function integrator of antioxidant defense across both lipophilic and hydrophilic compartments, bridging these two distinct modes of redox protection in the brain.